(untitled) (Bangladesh Journal of Urology, 2020)
Adrenal cysts are rare clinical condition that can present as abdominal swelling and chronic abdominal pain with weight loss. A 26 year old girl presented to our hospital with a 3 years history of right sided abdominal swelling and cachexia. Ultrasound of the abdomen reaveled a cystic area measuring 20x18 cm below the liver. Computed tomography scan showed a large cystic homogenous mass measuring 20x18x18.5cm in the right hypochondrium with most likely origin from the right adrenal gland. IVU showed left sided kidney was absent and left sided crossed ectopia was present. Both kidney on right side was pushed downwards. limited work up for hormone done. Hypersecretion was negative.A laparotomy with right adrenalectomy was performed. Final pathology showed a benign adrenal endothelial cyst.post operative period was unevenful. Surgical resection appears a safe and reasonable management strategy in a patient with adrenal cyst. Bangladesh Journal of Urology, Vol. 18, No. 1, Jan 2015 p.43-46